Insect Management for Onions, Leek, and Garlic - Susan E. Webb (EDIS, 2005)
Original Publication: Webb, Susan. 2002. “Insect Management for Onions, Leek, and Garlic”. EDIS 2002 (1). https://doi.org/10.32473/edis-ig153-2002.